Idiopathic Intracranial Hypertension – How Can Orthoptists Help Improve Care? - Daisy MacKeith (British and Irish Orthoptic Journal)
Care for people with idiopathic intracranial hypertension (IIH) needs improving and I think orthoptists are in a perfect position to help. The problems with IIH care are multi-fold: • People with fulminant IIH are still losing sight due to delayed diagnosis or mismanagement. • People with IIH often have a poor quality of life due to disabling chronic headaches and poor mental health. • There is a lack of access to evidence-based weight-loss interventions and support. • Weight stigma in healthcare remains pervasive and damaging and disproportionately impacts women. • Functional vision loss and headaches in IIH can complicate the interpretation of visual function which can have implications for management. • There is a lack of evidence to support treatment options. Below I will describe the issues in more detail and outline the ways in which we as orthoptists can help this patient group.